(untitled) (Journal of Nobel Medical College, 2021)
Background: Pelvic organ prolapse in elder women causes sufficient morbidity and decreased quality of life. Despite age related comorbidities and decreased physiological capabilities, elder women with pelvic organ prolapse may be benefitted by surgical repair via vaginal route.The purpose of this study is to evaluate the safety of vaginal repair of pelvic organ prolapse in women of age 60 years or older. Materials and Methods: This hospital based analytical study was carried out in Birat Medical College Teaching Hospital from September 2020 to September 2021. Fifty-four patients aged 60 years or older with third and fourth degree pelvic organ prolapse were recruited for the study. Necessary information was obtained by self-structured questionnaire and entered into Microsoft Excel. Data was analyzed by SPSS version 22. Results: Fifty-four women with third or fourth degree prolapse with cystocele and rectocele underwent vaginal hysterectomy with anterior colporrhaphy with posterior colpoperineorrhaphy. No organ injury occurred during operation. There was no mortality or severe intraoperative or postoperative complications. Conclusion: Vaginal hysterectomy with pelvic floor repair for pelvic organ prolapse in women of 60 years or older is safe.